Cytogenetic analysis of three catfish species of the family Pseudopimelodidae (Teleostei, Siluriformes) - Martinez, Emanuel Ricardo Monteiro [UNESP] (2008)
Cytogenetic analyses performed in Cephalosilurus apurensis, Microglanis aff. cottoides and Pseudopimelodus bufonius revealed that the three species have 2n = 54 chromosomes: C. apurensis presented six metacentric (M), 28 submetacentric (SM), 14 subtelolocentric (ST), and six acrocentric (A) chromosomes, while M. aff. cottoides showed 10M, 32SM, 10ST and 2A, and P. bufonius had 12M, 30SM and 12ST. The nucleolus organizer regions (NORs) were present on the short arm of a middle-sized ST pair, identified as pair 19, in C. apurensis NORs were found on the short arm of a middle-sized ST (pair 23) and on the long arm of a middle-sized ST (pair 22) in M. aff. cotttoides and on the short arm of three middle-sized ST pairs, identified as pairs 9, 10 and 11, in P. bufonius. C-banding revealed a very small amount of constitutive heterochromatin in the chromosomes of all species, including the NORs. The occurrence of 2n = 54 in all species of the family Pseudopimelodidae and its absence among species of the closely related Pimelodidae and Heptapteridae may be important in identifying Pseudopimelodidae species.